PERAN PEREMPUAN DALAM PEMBERDAYAAN HARTA PERSPEKTIF AL-QURâAN - Masse, Rahman Ambo (AL-MAIYYAH, 2015)
This paper examines the role of women in the empowerment of the property according to a review of the Koran. In view of the Koran, the property is one of the worldâs ornament which has attached to human. The role of women in various aspects of life is very interesting to be observed. In the world economy, Indonesian women actually already have equality with men. The real economic activity in real business such as in the traditional markets has dominated by the women. In West Sumatra, which adheres matriarkhat line, women master the customary property affairs since long time. In Bali, womens labor work not only on a soft job but also work on harsh work, such as brick-layer. The empirical evidence indicated that women have taken an important role in the management and wealth empowerment, not only in the realm of family, but also in the realm business activities, such as home industry and large-scale businesses.